The Sustainable Technological Innovation among SMEs in South East Asia Countries: A Case Study - Tan, CheeFai; Ranjit, S.S.S.; Ong, S.T; Ngeow, Y.W. (2011)
South East Asia (SEA) region is characterized by economies of vast disparities in natural resources, capabilities and development levels. Key issues for Small and Medium Enterprises (SMEs) in globalizing economies in the region continue to financing, marketing, technology, human resource and external environment including policy framework. SMEs are currently going through a transition phase and process of restructuring for competitive growth, in the fast technological changes, among other factors. The increasing influx of transnational corporations (TNCs) and foreign direct investment (FDI) in manufacturing and services in the region have opened up large business opportunities and also threats, needing more advanced technological inputs, and absorptive and innovative capabilities for enhancing and efficiency of SMEs. This paper describes the technological innovation, provide information, and discuss the technological innovation issues in selected SEA countries.